O brincar-e-se-movimentar: a linguagem da criança - Berleze, Daniele Jacobi (2016)
The child language consists of symbols and signs. One of its functions is the communication and dialogue, assisting in the construction and development of thought and knowledge. The child has many languages one of which is the "Play and Move." From this, comes this work in order to start the study and discussion of the theoretical knowledge about the child's language and its "Play and Move." Starting from a brief theoretical research, which is dedicated to formulating frames of reference, study, create and (re) formulating theories, namely improving knowledge. She bases and open the way for new productions. From this we can understand that the language of children is composed of multiple signs and symbols, acting as an important development tool. The first form of natural language of child's play and Move ", which is usually expressed and the bodily play a form of expressiveness inherent be. The "If-Move" is a form of "understanding-the-world-by-Act" and to communicate with the same and with people, so an "inherent human need". The language becomes a way to joke, and this becomes a form of language, being a dialogue with the world. This dialogical conception takes into account more subjective, spontaneous and free, present in essence and intuitiveness of the movement of the child.